2003
DOI: 10.1177/095965180321700601
|View full text |Cite
|
Sign up to set email alerts
|

Active constrained-layer damping: A state-of-the-art review

Abstract: In this paper the authors discuss the progress that has been made over the past decade in active constrained-layer damping (ACLD). ACLD treatments combine the best features of passive and active control of structural vibrations. By way of introduction the paper describes well-established techniques for passive control of structural vibrations and noise. A concise discussion of the development of so-called 'smart' (or 'intelligent') actuators and sensors and the emergence of suitable control algorithms show how… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
34
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(36 citation statements)
references
References 67 publications
0
34
0
Order By: Relevance
“…Hence plugging (20) in (19) yields Re A z, z H×H = D 0 z 2 , z 2 V ×V ≥ 0 by (14). We next verify the range condition.…”
Section: Stabilization Without Magnetic Effectsmentioning
confidence: 99%
See 1 more Smart Citation
“…Hence plugging (20) in (19) yields Re A z, z H×H = D 0 z 2 , z 2 V ×V ≥ 0 by (14). We next verify the range condition.…”
Section: Stabilization Without Magnetic Effectsmentioning
confidence: 99%
“…See other control strategies i.e. in [20], and the references therein. However, even in the case of a single piezoelectric beam, as the dynamic effects are kept, a strongly coupled wave system is obtained for which it is shown that the model is not controllable and not uniformly exponentially stabilizable for almost all combinations of material parameters with the B * −type feedback, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…A recent review article based upon active constrained layer damping [9] has distinguished between Independent Modal-Space Control, requiring collocation of sensor and actuator pairs, and coupled control. It was argued that coupled control requires fewer sensors and actuators to achieve the same performance.…”
Section: Active Dampingmentioning
confidence: 99%
“…Furthermore, a range of semi-active control systems have been used in the various structural vibration control applications which include the controllable fluids, ER fluid and MR fluid. They provide the enhanced damping properties with only minimal power requirement compared to active and passive systems due to their controllable rheology (Spencer and Nagarajaiah [3], See [4], Stanway et al [5], Xu et al [6]). …”
Section: Introductionmentioning
confidence: 99%